2-[(3-Aminoalkyl-(alkaryl-,aryl-))- 1 H-1,2,4-triazol-5-yl]anilines: synthesis and anticonvulsant activity - Martynenko, Yu.; Berest, G.; Bukhtiyarova, N.; Belenichev, I. F.; Voskoboinik, O.; Kovalenkо, S.; Мартиненко, Юлія Вікторівна; Берест, Галина Григорівна; Бухтіярова, Ніна Вікторівна; Беленічев, І.; Воскобойнік, Олексій Юрійович; Коваленко, Сергій Іванович (My University, 2020)
: The presented work is devoted to the development of synthesis methods for novel 2-[(3-aminoalkyl-(alkaryl-, aryl-))-1H -1,2,4-triazolo]anilines. Abovementioned compounds were obtained via hydrazinolysis (Ing-Manske procedure) and acid hydrolysis of corresponding N -acylated{([1,2,4]triazolo[1,5- c ]quinazolin-2-yl)alkyl-(alkaryl-, aryl-)}amines. The regioselectivity of hydrazinolysis and hydrolysis were established. The features of spectral characteristics were studied and discussed. Characteristic patterns of protons signals splitting in 1 H NMR of the synthesized compounds were established. The effect of the synthesized compounds on the pentylenetetrazol seizures was studied. It was found that according to some indicators, anticonvulsant activity of 2-[(3-aminoalkyl-(alkaryl-, aryl-))-1H -1,2,4-triazolo]anilines superior or comparable with effect of the reference drug “Lamotrigine”. It is a valid argument for their further structural modification, in-depth study of activity mechanisms and further study of anticonvulsant activity on other experimental seizures models.
Keywords: N -acylated{([1,2,4]triazolo[1,5- c ]quinazolin-2-yl)alkyl-(alkaryl-, aryl-)}amines; 2-[(3-aminoalkyl-(alkaryl-, aryl-))-1H -1,2,4-triazolo]anilines; hydrazinolysis; acidic hydrolysis; anticonvulsant activity